Microfinance and Women Entrepreneurship Development: The Moderating Role of Financial Literacy - Gurung, Tuk Raj (Kshitiz Management Review, 2026)
This study attempts to examine the role of microfinance services on women’s entrepreneurship development in Nepal and also analyzes the moderating effect of financial education in the relationship between microfinance services and women’s entrepreneurship development. Using a self administered questionnaire survey among 405 female micro-entrepreneurs, the results shows the savings behavior and skill development training as key drivers of women’s entrepreneurial advancement. In addition, the study also establishes that financial literacy has a nuanced moderating effect. As study postulates, skill development is more meaningful and the role of business support services is crucial in entrepreneurship outcomes. The findings from this study shed additional light to the literature by uncovering interplays between financial literacy, microfinance services, and women’s entrepreneurship in the context of small and developing economy of Nepal. The study also highlights the primary role of integrated financial education programs within microfinance initiatives and the importance of microfinance programs in achieving sustainable economic empowerment.